Hungry, hungry sharks - Cole, Joanna; Wynne, Patricia (New York Random House, 1986)
A simple discussion of the kinds of sharks and their behaviour.
"Grades 1-3."--Cover.
Keywords: Sharks -- Juvenile literature; Sharks